Aluminum component and method for manufacturing the same

By controlling the surface roughness parameters of the anodized coating and using a specific electrolyte, the complex process and white spot problems in the existing aluminum component manufacturing methods are solved, and the manufacturing of aluminum components with high whiteness and excellent appearance design is achieved.

CN113195797BActive Publication Date: 2025-02-18UACJ CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN201980080813.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-11-30
Filing Date
2019-11-21
Publication Date
2025-02-18
Estimated Expiration
2039-11-21

AI Technical Summary

Technical Problem

The existing aluminum component manufacturing method requires complicated processes such as secondary processing, making it difficult to obtain aluminum components with sufficient whiteness, and white spots are problematic, which affects the appearance designability.

Method used

By controlling the surface roughness parameters of the anodized coating, including the arithmetic average roughness Ra and the average length RSm of the roughness curve elements, combined with the anodized treatment of a specific electrolyte, a high whiteness can be obtained by one treatment. Aluminum member that inhibits white spots.

Benefits of technology

It is realized that an aluminum member with high whiteness and white spots are obtained through a simple one-time treatment, and the appearance designability and production efficiency of the aluminum member are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113195797B_ABST
    Figure CN113195797B_ABST
Patent Text Reader

Abstract

The object of the present invention is to provide an aluminum component and a method for manufacturing the same, wherein the aluminum component is obtained by a single treatment that is simpler than before, has high whiteness and suppressed white spots. The aluminum component to which the present invention relates comprises a base material formed of aluminum or an aluminum alloy, and an anodic oxide film formed on the surface of the base material, wherein the arithmetic mean roughness Ra of the aluminum component measured from the surface side of the anodic oxide film is greater than 0.1 μm, the average length RSm of the roughness curve element is less than 10 μm, and the Hunter whiteness is 60 to 90.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an aluminum component and a method for manufacturing the same, and in particular to an aluminum component having high whiteness and suppressed white spots that can be obtained through a simple one-time treatment without requiring complicated steps beyond secondary treatment and a method for manufacturing the same. Background Art

[0002] In applications such as building materials and electronic equipment housings that require lightweight and design, it is desirable to use opaque white aluminum components. However, conventional dyeing and coloring methods used in anodizing treatment of aluminum components are difficult to achieve such a color tone as opaque white. Therefore, research has been ongoing on how to produce aluminum-based materials with an opaque white color.

[0003] Patent Document 1 discloses a method for manufacturing an aluminum member having a white surface by changing the coating structure by performing porous anodizing treatment with current recovery after barrier anodizing treatment. Patent Document 2 discloses a method for coloring an aluminum member by filling a pigment into pores formed by anodizing treatment.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent document 1: Japanese Patent Publication No. 53-87945;

[0007] Patent document 2: Japanese Patent Application Publication No. 2017-25384. Summary of the invention

[0008] Problem that the invention aims to solve

[0009] However, the conventional method for manufacturing aluminum components with white surfaces further requires a complex electrolysis process such as a secondary treatment process or more. In addition, there is a problem in that expensive equipment must be invested in for AC electrolysis. Furthermore, the conventional method for manufacturing aluminum components cannot obtain aluminum components with sufficient whiteness. In addition, from the perspective of appearance design, it is desired to develop an aluminum component that suppresses white spots as much as possible and has excellent appearance characteristics.

[0010] The present invention has been developed in view of the above-mentioned problems, and an object of the present invention is to provide an aluminum member having high whiteness and suppressed white spots, which can be obtained by a single treatment simpler than conventional methods, and a method for producing the same.

[0011] Solutions for solving problems

[0012] The inventors of the present invention have conducted intensive research to solve the above-mentioned problems, and found that by appropriately controlling the surface roughness of the anodized coating, namely the arithmetic mean roughness Ra, and the lateral roughness parameter, namely the average length RSm of the roughness curve element, the whiteness of the aluminum component can be improved and white spots can be further suppressed.

[0013] Furthermore, the present inventors have found that by performing anodizing treatment on aluminum members using an electrolyte having a specific composition, an aluminum member having high whiteness and suppressed white spots can be obtained through a simple one-time treatment without requiring a complicated process of secondary treatment or higher.

[0014] An embodiment of the present invention is an aluminum component, which has a base material formed of aluminum or an aluminum alloy, and an anodized coating formed on the surface of the base material, the arithmetic mean roughness Ra of the aluminum component measured from the surface side of the anodized coating is greater than 0.1 μm, the average length RSm of the roughness curve element is less than 10 μm, and the Hunter whiteness is 60 to 90.

[0015] An embodiment of the present invention is an aluminum component, wherein the arithmetic mean roughness Ra and the average length RSm of the roughness curve element satisfy the relationship of 0.1≤Ra / RSm≤1.2, and the Hunter whiteness of the aluminum component measured from the surface side of the anodized film is 70-90.

[0016] An embodiment of the present invention is a method for manufacturing an aluminum component, comprising a step of preparing a base material formed of aluminum or an aluminum alloy, and a step of anodizing the base material in an electrolyte, wherein the electrolyte contains (a) a first acid or a salt thereof selected from the group consisting of an inorganic acid and an organic carboxylic acid, and (b) a second acid as an acid anhydride, wherein the concentration of the first acid or the salt thereof is 0.01 to 2.0 mol·dm -3 The concentration of the second acid is 0.01 to 5.0 mol·dm -3 .

[0017] An embodiment of the present invention is a method for manufacturing an aluminum member, wherein in the step of performing the anodizing treatment, the current density is 5 to 30 mA·cm -2 .

[0018] An embodiment of the present invention is a method for producing an aluminum member, wherein in the step of performing the anodizing treatment, the temperature of the electrolyte is 0 to 80°C.

[0019] An embodiment of the present invention is a method for producing an aluminum member, wherein in the step of performing the anodizing treatment, the electrolysis time is 10 to 600 minutes.

[0020] Effects of the Invention

[0021] According to the present invention, it is possible to provide an aluminum member having high whiteness and suppressed white spots, which can be obtained by a single treatment simpler than conventional methods, and a method for producing the same. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a schematic diagram schematically showing one embodiment of the aluminum member according to the present invention.

[0023] Figure 2 This is an image of a cross section of the anodized film of the aluminum member obtained in Example 3 captured by a scanning electron microscope (SEM). DETAILED DESCRIPTION

[0024] Hereinafter, embodiments of the present invention will be described. In addition, the present invention is not limited to the following embodiments, and can be implemented in various forms within the scope of the present invention.

[0025] <Aluminum components>

[0026] The aluminum member according to the present invention includes a base material and an anodic oxide film formed on the surface of the base material. Components of the aluminum member according to one embodiment will be described below.

[0027] (Base Material)

[0028] The base material can be any one as long as it is formed of aluminum or an aluminum alloy. The material of the base material can be appropriately selected according to the purpose of the aluminum component. For example, from the viewpoint of improving the strength of the aluminum component, the base material is preferably a 5000 series aluminum alloy or a 6000 series aluminum alloy. In addition, from the viewpoint of improving the whiteness of the aluminum component after anodizing, the base material is preferably a 1000 series aluminum alloy or a 6000 series aluminum alloy that is not easily colored by anodizing.

[0029] (anodized coating)

[0030] The anodic oxide coating has a barrier layer formed on the surface of the base material and a porous layer formed on the barrier layer. The thickness of the anodic oxide coating is not particularly limited, and the overall thickness is preferably 6 to 100 μm, more preferably 6 to 80 μm. If the thickness of the anodic oxide coating exceeds 100 μm, there is a tendency that the electrolysis time becomes longer, resulting in reduced productivity, and the occurrence of spots accompanied by uneven growth causes poor appearance.

[0031] The thickness of the barrier layer is not particularly limited, but is preferably 10 to 150 nm from the viewpoint of suppressing coloration due to interference and further improving whiteness.

[0032] The pores of the porous layer extend from the boundary between the porous layer and the barrier layer in the thickness direction of the porous layer. At this time, the pores may also branch out radially toward the surface of the porous layer in the thickness direction of the porous layer. That is, more than one pore may branch out from one pore within a specified angle range, such as extending more than one pore at a specified angle from one pore as it approaches the surface of the porous layer, and further extending more than one pore at a specified angle from the branched pore.

[0033] The thickness of the porous layer is not particularly limited. From the viewpoint of suppressing the coloring caused by interference and further improving the whiteness, it is preferably 6 μm or more and less than 100 μm, more preferably 8 to 75 μm, and more preferably 10 to 50 μm. When the thickness of the porous layer is less than 6 μm, the light diffusion caused by diffuse reflection is insufficient, so the anodized coating tends to become transparent. If the anodized coating becomes transparent, the overall color tone of the aluminum component is close to the color tone of the base material, so it is difficult to obtain the desired whiteness. In addition, the upper limit of the thickness of the porous layer is set to less than 100 μm, which is based on the upper limit of the thickness of the anodized coating, 100 μm.

[0034] Figure 1 Schematic diagram schematically showing one embodiment of the aluminum member according to the present invention. Figure 1 As shown, an anodic oxide film 2 is formed on the surface of a base material 1 made of aluminum or an aluminum alloy. The anodic oxide film 2 includes a barrier layer 3 formed on the surface of the base material 1 and a porous layer 4 formed on the barrier layer 3.

[0035] (Arithmetic mean roughness Ra)

[0036] The aluminum component has an arithmetic mean roughness Ra of 0.1 μm or more. Specifically, the arithmetic mean roughness Ra of the aluminum component measured from the surface side of the anodized film is 0.1 μm or more, preferably 0.5 μm or more, and more preferably 1.0 μm or more. The arithmetic mean roughness Ra of the roughness curve is the value obtained by folding the roughness curve in the concave-convex structure of the surface of the anodized film back from the center line and dividing the area obtained by the roughness curve and the center line by the unit length. It can also be said to represent the degree of specific surface area. The larger the arithmetic mean roughness Ra of the roughness curve of the aluminum component, the larger the area of ​​light scattering, and the whiter the aluminum component seen by the observer. This arithmetic mean roughness Ra can be measured, for example, according to JIS B0601: 2001. On the other hand, when the arithmetic mean roughness Ra is less than 0.1 μm, the inherent color tone of the aluminum component cannot be reduced because the light scattering area is small. As a result, the light irradiated to the anodized film cannot be fully scattered, making it difficult to obtain an aluminum component with high whiteness.

[0037] The aluminum component has an average length RSm of the roughness curve element of less than 10 μm. Specifically, the average length RSm of the roughness curve element of the aluminum component measured from the surface side of the anodized coating is less than 10 μm, preferably less than 8.0 μm, and more preferably less than 6.0 μm. The average length RSm of the roughness curve element represents the period of the concave-convex structure with a height difference of more than a certain level (the average interval of the concave-convex). The smaller the average length RSm of the roughness curve element of the aluminum component, the larger the area of ​​light scattering, and the whiter the aluminum component appears to the observer. The average length RSm of such a roughness curve element can be measured, for example, according to JIS B0601:2001. If the average length RSm of the roughness curve element of the aluminum component exceeds 10 μm, the area of ​​light scattering is small, so that the inherent color tone of the aluminum component is easily expressed. As a result, the light irradiated to the anodized coating cannot be scattered evenly, and white spots are easily generated in the aluminum component.

[0038] The aluminum component has a Hunter whiteness of 60 to 90. Specifically, the Hunter whiteness of the aluminum component measured from the surface side of the anodized coating is 60 to 90, preferably 70 to 90, and more preferably 80 to 90. In addition, Hunter whiteness refers to a value measured by the Hunter whiteness test method obtained according to the specification of JISP8123. The larger the Hunter whiteness, the higher the whiteness (opaque whiteness) of the aluminum component. By having a high Hunter whiteness of 60 to 90 for the aluminum component, the aluminum component has a suitable opaque white color, and can be given an excellent appearance design.

[0039] Regarding the ratio of the arithmetic mean roughness Ra to the average length RSm of the roughness curve element, the relationship between the arithmetic mean roughness Ra and the average length RSm of the roughness curve element preferably satisfies 0.1≤Ra / RSm≤1.2, more preferably satisfies 0.2≤Ra / RSm≤1.1, and further preferably satisfies 0.3≤Ra / RSm≤1.0. The ratio Ra / RSm of the arithmetic mean roughness Ra representing the roughness in the height direction and the average length RSm of the roughness curve element representing the lateral roughness represents the sharpness of the roughness curve. When the relationship between the arithmetic mean roughness Ra and the average length RSm of the roughness curve element satisfies 0.1≤Ra / RSm≤1.2, the light irradiated to the anodized coating can be effectively scattered, and since the Hunter whiteness is improved, the aluminum component appears whiter to the observer.

[0040] <Manufacturing method of aluminum member>

[0041] The manufacturing method of the aluminum component involved in the present invention includes the steps of preparing a base material and performing an anodizing treatment on the base material in a specific electrolyte. That is, as long as the specified anodizing treatment is performed as a primary treatment, there is no need to perform further secondary or tertiary treatments such as using other electrolytes different from the primary treatment or other complex treatments after the anodizing treatment, and an aluminum component with the desired high whiteness can be produced. Therefore, in the manufacturing method of the aluminum component involved in the present invention, an aluminum component with high whiteness can be provided through a simple primary treatment, so that the aluminum component with high whiteness can be manufactured more efficiently. Below, each step in the manufacturing method of the aluminum component involved in one embodiment is described in detail.

[0042] (Process of preparing base material)

[0043] First, a base material made of aluminum or an aluminum alloy is prepared. The aluminum alloy is not particularly limited, and examples thereof include 1000 series aluminum alloys, 5000 series aluminum alloys, and 6000 series aluminum alloys as described above.

[0044] (Process of anodizing the base material)

[0045] The base material is anodized in an electrolyte, wherein the electrolyte comprises (a) a first acid or a salt thereof selected from the group consisting of an inorganic acid and an organic carboxylic acid, and (b) a second acid as an acid anhydride. An anodic oxide film is formed on the surface of the base material by anodizing, the anodic oxide film having a barrier layer of a predetermined thickness, and a porous layer having a predetermined thickness is formed on the barrier layer. The conditions for the anodizing treatment are preferably set so that the anodic oxide film is formed as a whole to a thickness of 6 to 100 μm on the surface of the base material.

[0046] The first acid or its salt selected from the group consisting of inorganic acids and organic carboxylic acids is mainly used to form a film on the surface of the base material and dissolve it, and the second acid as an acid anhydride is mainly used to dissolve and re-form on the surface of the anodic oxide film. Thus, by using an electrolyte containing both a specific first acid or its salt and a specific second acid in an anodic oxidation treatment, these substances can act synergistically, and an aluminum component with excellent appearance design and Hunter whiteness of 60 to 90 can be produced by a single treatment according to the anodic oxidation treatment.

[0047] The inorganic acid or salt thereof as the first acid is not particularly limited, and examples thereof include at least one inorganic acid or salt thereof selected from the group consisting of sulfuric acid, phosphoric acid, chromic acid, and salts thereof.

[0048] Examples of the organic carboxylic acid or its salt as the first acid include oxalic acid, cyclic oxocarboxylic acid, tartaric acid, maleic acid, and salts thereof. The cyclic oxocarboxylic acid is preferably croconic acid, rhodiolacid, or squaric acid.

[0049] The anhydride of the anhydrous acid not containing hydrate as the second acid is not particularly limited, and at least one anhydride selected from the group consisting of trimellitic anhydride, phthalic anhydride, maleic anhydride, pyromellitic anhydride, diphosphoric acid, triphosphoric acid and polyphosphoric acid can be cited. Among these anhydrides, from the viewpoint of easy stable treatment by buffering effect, at least one anhydride selected from the group consisting of diphosphoric acid, triphosphoric acid and polyphosphoric acid is preferred.

[0050] The concentration of the first acid or its salt in the electrolyte is 0.01 to 2.0 mol·dm -3 , preferably 0.05 to 1.5 mol·dm -3 When the concentration of the first acid or its salt is less than 0.01 mol·dm -3 When the anodizing treatment of the base material cannot be carried out uniformly over the entire treatment area, and the light irradiated to the anodized film cannot be evenly scattered, poor appearance (white spots) is likely to occur. On the other hand, if the concentration of the first acid or its salt exceeds 2.0 mol·dm -3 , the viscosity of the solution increases and it is difficult to evenly perform anodizing of the base material over the entire treatment area. In addition, since the solubility of the electrolyte becomes higher, the current density becomes too high to grow the anodized film, thereby increasing the average roughness RSm of the roughness curve element. As a result, it is impossible to evenly scatter light, and poor appearance (white spots) is likely to occur.

[0051] The concentration of the second acid in the electrolyte mainly contributes to the arithmetic mean roughness Ra and is 0.01 to 5.0 mol·dm -3 , preferably 0.1 to 2.5 mol·dm -3 The concentration of the second acid is less than 0.01 mol·dm -3 When the concentration of the second acid exceeds 5.0 mol·dm -3 , the viscosity of the solution increases, making it difficult to evenly perform anodizing of the base material over the entire treatment area, and poor appearance (white spots) is likely to occur. Therefore, by controlling the concentration of the second acid to 0.01 to 5.0 mol·dm -3 Within the range, an aluminum component with high whiteness, uniform surface roughness curve and excellent appearance design can be obtained.

[0052] The electrolysis time during anodizing mainly contributes to arithmetic mean roughness Ra, and is preferably 10 to 600 minutes, and more preferably 30 to 300 minutes. When the electrolysis time is less than 10 minutes, the film thickness of the anodized coating is thin, and the tendency of the anodized coating of the desired thickness cannot be obtained. On the other hand, even if the electrolysis time exceeds 600 minutes, the arithmetic mean roughness Ra will not change substantially, and the production efficiency is poor, so it is not preferred.

[0053] The current density during the anodizing treatment mainly contributes to the average roughness RSm of the roughness curve element and is preferably 5 to 30 mA·cm -2 , more preferably 10 to 30 mA·cm -2 By setting the current density to 5 mA·cm -2 The above can accelerate the film formation speed of the anodized film and obtain an anodized film of sufficient thickness at the same time. In addition, by setting the current density to 30 mA cm -2 Hereinafter, the formation and dissolution of the anodic oxide film on the surface of the base material can be more densely performed, and the average roughness RSm of the roughness curve element can be suppressed from becoming excessively large.

[0054] The temperature (liquid temperature) of the electrolyte during anodizing treatment mainly contributes to the average roughness RSm of the roughness curve element, preferably 0 to 80°C, more preferably 20 to 80°C. By making the temperature of the electrolyte above 0°C, the film formation rate of the anodized film can be accelerated, and at the same time, an anodized film of sufficient thickness can be obtained. In addition, by making the temperature of the electrolyte below 80°C, the formation and dissolution of the anodized film can be carried out more densely on the surface of the base material, and the average roughness RSm of the roughness curve element can be suppressed from becoming too large.

[0055] Therefore, by adjusting the conditions of the anodizing treatment, especially adjusting the concentration of the first acid or its salt, the concentration of the second acid in the electrolyte, as well as the electrolysis time, current density and temperature of the electrolyte during the anodizing treatment, the ratio Ra / RSm representing the sharpness of the roughness curve can be controlled within the desired range.

[0056] Before anodizing, the base material may be subjected to basic treatments such as degreasing and grinding as needed. For example, alkaline degreasing as a basic treatment can reduce the glossiness of the anodized coating and obtain a matte white aluminum component. On the other hand, grinding treatments such as chemical grinding, mechanical grinding, and electrolytic grinding as a basic treatment can improve the glossiness of the anodized treatment and obtain a bright white aluminum component. From the viewpoint of further improving the whiteness and glossiness of the aluminum component, it is preferred to perform electrolytic grinding on the base material before anodizing. In addition, after the base material is anodized, post-treatments such as sealing treatment may be performed as needed.

[0057] Example

[0058] The present invention will be described in detail below based on examples. The present invention is not limited to the examples shown below, and the configurations thereof may be appropriately changed within a range that does not impair the gist of the present invention.

[0059] A base material formed of an aluminum alloy as shown in Tables 1 and 2 below was prepared, and the base material was anodized under the conditions shown in Tables 1 and 2 to produce aluminum components of Examples 1 to 34 and Comparative Examples 2 to 8. On the other hand, in Comparative Example 1, the base material was not anodized. In Table 1, "1100" described as the type of base material alloy is a 1000 series aluminum alloy, "5052" is a 5000 series aluminum alloy, and "6063" is a 6000 series aluminum alloy. In addition, as basic treatments, alkaline degreasing was performed using 5% by mass of NaOH, chemical grinding was performed using a solution in which phosphoric acid and sulfuric acid were mixed in a volume ratio of 7:3, mechanical grinding was performed using a polishing grinder, and electrolytic grinding was performed using a solution in which glacial acetic acid and perchloric acid were mixed in a volume ratio of 4:1.

[0060] [Table 1]

[0061]

[0062] [Table 2]

[0063]

[0064] The aluminum components of Examples 1 to 34 and Comparative Examples 1 to 8 prepared according to Tables 1 and 2 were subjected to the following measurements and evaluations. The measurement and evaluation results are shown in Tables 3 and 4. Hunter whiteness, white spots, and roughness of the anodized coating were measured as follows. Regarding the "Judgment" in Tables 3 and 4, "◎" is set when there are no white spots and the Hunter whiteness is 70 or more, "○" is set when there are no white spots and the Hunter whiteness is 60 or more and less than 70, and "×" is set when the Hunter whiteness is less than 60 and / or there are white spots.

[0065] <Hunt Whiteness>

[0066] The obtained aluminum member was measured using a colorimeter for L standardized by the International Commission on Illumination (CIE) specified in JIS Z8781-4:2013. * a * b * , and converted into Hunter whiteness according to the following formula for evaluation.

[0067] Hunter whiteness = 100-{(100-L * ) 2 +a *2 +b *2}1 / 2 .

[0068] <White spots>

[0069] Visually observe the appearance of the samples of each embodiment and comparative example after anodizing. 2 The appearance of the sample was evaluated as follows, and the case where the anodization was uniform was evaluated as "○", and the case where white spots occurred or the anodization was not performed was evaluated as "×".

[0070] <Roughness of anodized coating>

[0071] For the samples of each embodiment and each comparative example after anodizing, the surface roughness of the anodized film was measured using a laser microscope ("LEXT-OLS3000", manufactured by Olympus Corporation). At this time, within the field of view of 128μm×96μm at any part of the surface of the anodized film, three line analyses were performed horizontally and parallel to the rolling grain direction, and the average value of a total of 6 times was calculated. The above measurements were performed in 5 fields of view, and the average value was calculated as the arithmetic mean roughness Ra and the average length RSm of the roughness curve element. In addition, the value obtained by dividing the calculated arithmetic mean roughness Ra by the average length RSm of the roughness curve element is used as the sharpness Ra / RSm of the roughness curve.

[0072] [Table 3]

[0073]

[0074] [Table 4]

[0075]

[0076] Figure 2 : This is an image of a cross section of an anodic oxide film included in the cross section of the aluminum member produced in Example 3, which was photographed using a scanning electron microscope (SEM). Figure 2 As shown, it can be seen that the aluminum member of Example 3 has an anodic oxide film 2 formed on the base material 1 .

[0077] As shown in Tables 1 and 3, in the aluminum components of Examples 1 to 34 obtained by anodizing a base material formed of an aluminum alloy in an electrolyte containing a specified first acid or its salt, and a specified second acid, it was confirmed that an anodic oxide film was formed on the surface of the base material. In addition, in the aluminum components of Examples 1 to 34, the arithmetic mean roughness Ra is greater than 0.1 μm, the average length RSm of the roughness curve element is less than 10 μm, the Hunter whiteness is 60 to 90, and the white spot evaluation is "○". Therefore, in Examples 1 to 34, aluminum components with high whiteness and excellent appearance characteristics can be obtained by suppressing the occurrence of white spots. In particular, in Examples 3 to 34, a high Hunter whiteness of more than 70 is exhibited, so that aluminum components with higher whiteness can be obtained.

[0078] On the other hand, in Comparative Example 1, the base material was only alkali-degreased using 5 mass % NaOH as a basic treatment, and no anodizing treatment was performed. Therefore, the base material was not anodized, and no anodized film was formed, and the Hunter whiteness of the obtained aluminum member was low.

[0079] In Comparative Example 2, the concentration of the material corresponding to the first acid or its salt in the electrolyte was too low, so the anodic oxidation treatment of the base material could not be uniformly performed over the entire treatment area. In addition, since the electrolyte did not contain the material corresponding to the second acid, the arithmetic mean roughness Ra became small, and light could not be fully scattered. As a result, white spots occurred in the obtained aluminum component, and the Hunter whiteness was also low.

[0080] In Comparative Example 3, since the concentration of the material corresponding to the second acid in the electrolyte was too low, the arithmetic mean roughness Ra became small and light could not be sufficiently scattered. Therefore, although the anodization was uniform in the obtained aluminum member, the Hunter whiteness was low.

[0081] In Comparative Example 4, since the material equivalent to the first acid or its salt is excessive in the electrolyte, the viscosity of the solution increases and the anodizing treatment of the base material cannot be uniformly performed over the entire treatment area. In addition, since the solubility of the electrolyte becomes high and the current density is too high to grow the anodized film, the average roughness RSm of the roughness curve element becomes large, and light cannot be fully scattered. Therefore, white spots occur in the obtained aluminum component, and the Hunter whiteness is also low.

[0082] In Comparative Example 5, since the material equivalent to the first acid or its salt is excessive in the electrolyte, the viscosity of the solution increases and the anodic oxidation treatment of the base material cannot be uniformly performed over the entire treatment area. In addition, since the solubility of the electrolyte becomes high and the current density is too large to grow the anodic oxide film, the average roughness RSm of the roughness curve element becomes large. In addition, the electrolyte does not contain the material equivalent to the second acid, so the arithmetic mean roughness Ra becomes smaller, and the light cannot be fully scattered compared with Comparative Example 4. Therefore, white spots occur in the obtained aluminum component, and the Hunter whiteness is also low.

[0083] In Comparative Example 6, although Ra / RSm satisfies the prescribed range, the electrolyte does not contain a material corresponding to the second acid, so the arithmetic mean roughness Ra becomes small and light cannot be fully scattered. Therefore, the obtained aluminum member is uniformly anodized but cannot obtain high Hunter whiteness.

[0084] In Comparative Example 7, since the material equivalent to the first acid or its salt is excessive in the electrolyte, the viscosity of the solution increases and the anodizing treatment of the base material cannot be uniformly performed over the entire treatment area. In addition, since the solubility of the electrolyte becomes higher and the current density is too large to grow the anodized film, the average roughness RSm of the roughness curve element becomes larger, but Ra / RSm is within the specified range. Therefore, the light irradiated to the anodized film can be effectively scattered, and the Hunter whiteness is improved. As a result, although a high Hunter whiteness can be obtained in the obtained aluminum component, white spots occur.

[0085] In Comparative Example 8, although Ra and RSm meet the specified values, the material equivalent to the second acid in the electrolyte is excessive, so the solution viscosity increases and the anodizing treatment of the base material cannot be uniformly performed over the entire treatment area. On the other hand, since Ra / RSm is within the specified range, the light irradiated to the anodized film can be effectively scattered, and the Hunter whiteness is improved. Therefore, although a high Hunter whiteness can be obtained in the obtained aluminum component, white spots occur.

[0086] Description of Reference Numerals

[0087] 1 base material; 2 anodized coating; 3 barrier layer; 4 porous layer.

Claims

1. An aluminum component, characterized in that: have: A base material formed of aluminum or an aluminum alloy, and an anodic oxide film formed on the surface of the base material, The aluminum member has an arithmetic mean roughness Ra of 0.1 μm or more, an average length RSm of a roughness curve element of 10 μm or less, and a Hunter whiteness of 60 to 90 as measured from the surface side of the anodized film.

2. The aluminum member according to claim 1, wherein The arithmetic mean roughness Ra and the average length RSm of the roughness curve element satisfy the relationship of 0.1≤Ra / RSm≤1.2, and the Hunter whiteness of the aluminum member measured from the surface side of the anodized film is 70 to 90.

3. The method for manufacturing an aluminum member according to claim 1 or 2, characterized in that: have: A process of preparing a base material formed of aluminum or an aluminum alloy; and The step of anodizing the base material in an electrolyte solution containing (a) a first acid or a salt thereof selected from the group consisting of an inorganic acid and an organic carboxylic acid, and (b) a second acid which is an acid anhydride, The first acid or its salt is an acid or its salt selected from the group consisting of inorganic acids and organic carboxylic acids, the inorganic acid or its salt is at least one inorganic acid or its salt selected from the group consisting of sulfuric acid, phosphoric acid, chromic acid and their salts, and the organic acid or its salt is selected from oxalic acid, cyclic oxocarboxylic acid, tartaric acid, maleic acid and their salts. The second acid is at least one anhydride selected from the group consisting of trimellitic anhydride, phthalic anhydride, maleic anhydride, pyromellitic anhydride, diphosphoric acid, triphosphoric acid and polyphosphoric acid, The concentration of the first acid or its salt is 0.01 to 2.0 mol / dm 3 , The concentration of the second acid is 0.01 to 5.0 mol / dm 3 , In the anodizing step, the current density is 5 to 30 mA / cm 2 , the temperature of the electrolyte is 0-80°C, and the electrolysis time is 10-600 minutes.

Citation Information

Patent Citations

  • Whitening treatment method of surface of aluminium or aluminium alloy material

    JP1978087945A

  • Colored aluminum molded body and method for producing the same

    JP2017025384A

  • Dry adhesives

    CN103732527A

  • White appearing anodized films and methods for forming the same

    CN107815713A